Torsional behavior of a friction welded martensitic stainless steel - Kati, Nida; Ozan, Sermin (Carl Hanser Verlag, 2016)
Being widely used in automotive, machinery, aviation and aerospace industry, solid-sate friction welding was applied in this study. AISI 420 martensitic stainless steel, being difficult to be joined by using fusion welding methods, was joined by friction welding. During the welding process, three rotational speeds (R) of 700, 1000 and 1300 rpm were used and other parameters such as friction pressure (Fp), friction time (Ft), upsetting pressure (Up) and upsetting duration (Ud) were kept constant. After the welding process, a torsion test was performed with these samples. The torsion angle (Ta) - torque (T) graphics of the samples were evaluated. Additionally, the fracture surface of the samples was examined by using SEM. As a result, it was observed that the AISI 420 steel was welded without problems by using friction welding. During the torsion tests, the samples fractured outside the welded joint zones. Thus, it was concluded that torsional strength of the welded joints was high.
Keywords: Friction welding; AISI 420; torsion; fracture behavior